Effect of oxidation with coagulation and ceramic microfiltration pre-treatment on reverse osmosis for desalination of recycled wastewater - Myat, D.; Roddick, F.; Puspita, P.; Skillman, L.; Charrois, Jeffrey; Kristiana, Ina; Uhl, W.; Vasyukova, E.; Roeszler, G.; Chan, A.; Zhu, B.; Muthukumaran, S.; et al. (Elsevier BV, 2017)
© 2017 Elsevier B.V. Oxidation and coagulation before ceramic microfiltration (CMF) greatly increases membrane flux, but is unconventional for reverse osmosis (RO) pre-treatment. Impacts to RO and the wastewater recycling scheme operating CMF at high flux conditions is little understood. In this work, wastewater was treated with ozone or ultraviolet/hydrogen peroxide (UVH) oxidation, coagulation, then CMF, to explore RO membrane performance at bench scale. Sustainable high CMF fluxes were confirmed using coagulation with either ozone or UVH. Uniquely for ozone, dosing 13mg-O 3 /L for 15min greatly increased toxic by-product N-nitrosodimethylamine (NDMA) to 33ng/L. Dosing chloramine (common for RO biofouling control) added only up to 7ng/L NDMA. RO tests on all pre-treated waters showed little variation to flux but oxidation significantly altered texture of RO fouling material from smooth and dense to porous and granular. Biofouling studies with model bacteria strain RO 22 (Pseudoalteromonas spp) showed higher organic biodegradability but biofilm analysis revealed ozone-coagulant-CMF greatly limited extension of bacteria communities from the membrane surface suggesting oxidation reduces RO biofouling. The novel findings of reduction of RO biofouling risk with oxidation and coagulation for high flux CMF pre-treatment identified in this work need to be demonstrated on different wastewater types over longer term.